Can temporal self-regulation theory and its constructs predict medication adherence? A systematic review and meta-analysis - Liddelow, Caitlin; Mullan, Barbara; Boyes, Mark; Ling, M. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The relationships between temporal self-regulation theory (TST) constructs (intention, behavioural prepotency and self-regulatory capacity) and medication adherence should be established before further applying the theory to adherence. Searches of PsychINFO, Medline, EMBASE, CINAHL and Web of Science were conducted in 2019 (updated November 2021). Studies had to be original quantitative research, assessed the relationship between one of the constructs and adherence in one illness, and used an adult population. The risk of bias was assessed using the NHLBI Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Three meta-analyses were conducted using R. Moderation analyses were also conducted. A total of 57 articles (60 studies) with 13,995 participants were included, with 7 studies included in more than one analysis. Results identified significant correlations between intention (r =.369, [95% CI:.25,.48]), behavioural prepotency (r =.332, [95% CI:.18,.48]), self-regulatory capacity (r =.213, [95% CI:.10,.32]) and adherence. There was some evidence of publication bias and no significant moderators. No studies explored the interactions in the theory, so whilst the constructs adequately predict adherence, future research should apply the theory to adherence in a specific illness to assess these relationships. Pre-registered on Prospero: CRD42019141395.